Help seeking behaviors among international higher education students - Mambo, Andrew (2019)
The aim of this study is to identity the help seeking behaviors among higher education students. The underlying assumption is that international students of all caliber face one issues or another during their sojourn in a different country. The study looks at acculturation as studied over the years in relation to international students then goes to tackle the coping strategies as used by foreign students. The study is qualitative in nature. Eight interviews were conducted and the data analyzed through the deductive method. The findings show that higher education students rely on formal and informal networks for support during their stay in Finland. This paper offers recommendations on how these channels can be better utilized by universities to extend help to students.